Stability Analysis and Synthesis for Networked Systems with Noisy Sampling Intervals, Random Transmission Delays and Packet Dropouts - Hu, Zhipei; Deng, Feiqi; Su, Yongkang; Luo, Shixian; Liu, Yu; Chen, Kai (IEEE transactions on automatic control, 2024)
In this article, we study the stability analysis and H_{∞ } controller synthesis problems for networked systems with random transmission delays and packet dropouts that are subject to noisy sampling intervals. The sampling errors and transmission delays are described by an independent and identically distributed sequence of continuous random variables and the transmission delays are assumed to be smaller than the noisy sampling intervals. First, a closed-loop discrete-time stochastic framework for networked system that allows investigating noisy sampling intervals, random transmission delays and packet dropouts simultaneously is established. To render the discrete-time stochastic system suitable for stability analysis and synthesis, an equivalent yet tractable stochastic augmented model is then reformulated with the help of matrix exponential computation. Based on this augmented model, a stability condition involving the expectation of a nonlinear and random coupling matrix is derived. By recurring to the law of total expectation and Kronecker product operation, the expectation operation of the coupling matrix subject to high nonlinearity and multiple randomness is decoupled. Subsequently, a controller algorithm is designed such that the exponential mean-square stability of the original discrete-time stochastic system with a prescribed H_{∞ } performance is guaranteed. Finally, an example is provided to illustrate the effectiveness of the controller design algorithm.